PENGARUH EMOTIONAL INTELLIGENCE TERHADAP ORGANIZATIONAL PERFORMANCE : PERAN MEDIASI SELF-EFFICACY - Rusiha Minanda Pratiwi; Jeni Wardi; Adi Rahmat (Indragiri Research Center (ingreat), 2025)
Previous studies have shown that emotional intelligence plays an important role in the educational environment, especially in supporting the psychological well-being of educators. However, research linking emotional intelligence to organizational performance (OP) in the public sector is still lacking, especially among public policy management. This research is a type of quantitative descriptive research with a causal research design with a population of state civil servants at the Siak Regency Health Office with a population of 64 people. The sampling method used in this study is the saturated sampling method. The saturated sampling method is a sampling technique when all members of the population are used as samples. Data collection techniques using questionnaires and distribution using google forms. The data analysis tool in this study is Structural Equation Modeling (SEM) processed using SmartPLS 32.9 for data processing. From the findings of this study, it was found that emotional intelligence has a positive and significant effect on organizational performance (hypothesis 1 is rejected), emotional intelligence has a positive and significant effect on self-efficacy (hypothesis 2 is accepted), self-efficacy has a positive and significant effect on organizational performance (hypothesis 3 is accepted) and emotional intelligence has a positive and significant effect on organizational performance through self-efficacy (hypothesis 4 is accepted).